Pedagogika „łejerska” – próba syntezy u progu 50-lecia jej istnienia - Sadowska, Katarzyna (Pedagogika Społeczna Nova, 2025)
“Łejery” pedagogy, which has existed for almost 50 years, is a topic worth considering because it is a unique phenomenon in Poland, which resulted in the establishment of Primary School No. 83 on September 1, 1990. Emilia Waśniowska in Poznań has had a professional theatre since 2013 (the Common Stage of the facility and the Poznań Children’s Art Center). The study aims to synthetically present the most important assumptions of “Łejery” pedagogy on the threshold of the 50th anniversary of its existence. To achieve the goal, the method of analysing existing and retrieved sources was used, including diploma theses available in university repositories, doctoral thesis (unofficial version obtained from the author) by Katarzyna Moskiewicz prepared at the Faculty of History of Adam Mickiewicz University, press materials, information obtained by Katarzyna Sadowska during conversations conducted at Primary School No. 83 in Poznań with Jerzy Hamerski and Elżbieta Drygas,as well as electronic sources related to the facility and studies and articles from periodical publications. The current state of research on “Łejery” pedagogy is insufficient. So far, only one scientific work mentioned above has been published (doctoral dissertation), which describes Primary School No. 83 in Poznań as an alternative school and discusses it in a comparative context with other schools established during the political transformation in Poland, and only a few works have been written diploma students of pedagogical faculties of selected Polish universities.